Answer:
Explanation:
1. (x - 3)(x + 7) = 0
By zero product property,
(x - 3) = 0 ⇒ x = 3
(x + 7) = 0 ⇒ x = -7
2. (2x + 6)(x - 7) = 0
2(x + 3)(x - 7) = 0
By zero product property,
(x + 3) = 0 ⇒ x = -3
(x - 7) = 0 ⇒ x = 7
3). (4x - 2)(x + 4) = 0
2(2x - 1)(x + 4) = 0
(2x - 1) = 0 ⇒ x =
![(1)/(2)](https://img.qammunity.org/2021/formulas/physics/middle-school/ukxexrkoplrwscaxd96qbbkphc5fo6w2ur.png)
(x + 4) = 0 ⇒ x = -4
4. (5x - 1)(3x + 9) = 0
3(5x - 1)(x + 3) = 0
By zero product property,
(5x - 1) = 0 ⇒ x =
![(1)/(5)](https://img.qammunity.org/2021/formulas/mathematics/high-school/nve42zwxkm2ttkh80stksgu37lazt1jlhm.png)
(x + 3) = 0 ⇒ x = -3
5. (x - 8)(x + 2) = 0
By zero product property,
(x - 8) = 0 ⇒ x = 8
(x + 2) = 0 ⇒ x = -2